(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: This research aims to demonstrate the impact of the tax assessor’s skills with its dimensions represented by (scientific and qualifying skills, technical and functional skills, personal skills, professional competence, dealing with others and communicating with them) on the quality of tax accounting. The role of the tax assessor has become a vital and important role in the tax process and has a major impact on the tax revenue. From this standpoint, the focus on studying the role of the tax assessor in its various dimensions has become an urgent and necessary need. To prove the research hypothesis, the questionnaire was designed as a main tool for collecting data, and (150) questionnaires were distributed. It included 150 respondents from employees (assessors) in the General Tax Authority and some of its branches in Baghdad Governorate, who represented the population and sample of the research, and the answers were analyzed based on the statistical program (SPSS V.23).In addition, the financial reports for the year (2020) were analyzed for a different group of companies in various sectors that were randomly selected as case studies to demonstrate the relationship between the skills of the tax assessor and the quality of tax accounting. The research reached a set of conclusions, and the most prominent of these conclusions is that there is a significant, statistically significant effect on the skills of the tax assessor at different levels on the quality of tax accounting. The most important recommendations recommended by the research were the development of a strategic plan and program to develop the skills and enhance the attributes of the tax assessor